Meta-equilibrium transition microstructure for maximum austenite stability and minimum hardness in a Ti-stabilized supermartensitic stainless steel. (15th October 2018) - Escobar, J.D.; Oliveira, J.P.; Salvador, C.A.F.; Faria, G.A.; Poplawsky, J.D.; Rodriguez, J.; Mei, P.R.; Babu, S.S.; Ramirez, A.J.
Abstract: The maximization of stable reverted austenite at room temperature through inter-critical tempering is a widely used method to reduce hardness in supermartensitic stainless steels. Nevertheless, partial martensitic transformation might occur due to insufficient compositional stabilization. In this work, we conducted a time-resolved triple-step inter-critical tempering, specially designed to obtain maximum austenite stability and minimum hardness through the progressive suppression of the martensitic transformation. The mechanism behind the progressive increase in stable reverted austenite was the generation of a meta-equilibrium state, which imposed a limit in both high temperature austenite reversion and room temperature austenite stabilization. Such limit corresponded to the high temperature volume fraction of austenite, obtained right before cooling from the first cycle. This effect was associated to the Ni-rich fresh martensite laths acting as local Ni compositional pockets, providing site-specific austenite reversion; and to the suppression of any additional nucleation at the Ni-poor matrix as the T0 temperature for austenite reversion was strongly increased. The softening mechanism was mainly controlled by the carbon arrest effect by the precipitation of Ti (C, N), which was completed after the first tempering cycle. Nevertheless, maximizing reverted austenite and suppressing fresh martensite at room temperature did not result in additional hardness reductions. Graphical abstract: Unlabelled Image Highlights: Compositional gradients after single tempering forced a meta-equilibrium during the second and third tempering cycles. Nucleation at the Ni-poor tempered matrix was suppressed. Site-specific austenite reversion occurred at the Ni-rich fresh martensite laths. The softening mechanism was insensitive to the maximization of austenite after double and triple tempering.